Relationship Between Necrosis, Neovascularization, and Lymphocyte Reaction in Histopathological Types of Cervical Cancer - Jamilah, Qurratu Kasturi; Lubis, Humairah Medina Liza (Universitas Muhammadiyah Sumatera Utara, 2024)
Abstract: Cervical cancer is a malignant tumour that grows on the cervix, more than 90% of which are caused by HPV 16 and 18. lymphocytes are one of the immune systems that play a role in immunosurveillance against cancer cells. However, cervical cancer will cause necrosis and activate Hypoxia-Inducible Factor-1 (HIF-1) which plays a role in the formation of neovascularization. Based on histopathological findings, cervical cancer types are classified into squamous cell carcinoma (SCC) and adenocarcinoma (ADC). This study aimed to determine the relationship between necrosis, neovascularization, and lymphocyte reaction in various histopathological types of cervical cancer. This research is observational analysis using medical records and histopathological slides of patients diagnosed with cervical cancer. There were 26 cases of cervical cancer consisting of 16 types of SCC and 12 types of ADC. Based on the highest percentage, more necrosis was found in ADC 81.8% (p-value 0.014), neovascularization in SCC 73.3% (p-value 0.014), and lymphocyte reaction in SCC 86.7% (p-value 0.973). This means that there was a significant relationship between necrosis and lymphocyte reaction in various histopathological types of cervical cancer, however, there is no significant relationship between neovascularization in various histopathological types of cervical cancer.